The Leadership role – Twitter’s Ups and down since 2006: change in leadership - Chacko, elizabeth; Nair, Sridevi; Mathew, Jain (IIUM Journal of Case Studies in Management, 2024)
Elon Musk bought Twitter in the month of October of 2022 and as of January 2023, Twitter is looking for its next CEO. While change in leadership is not something new in this dynamic environment, the effects of change cannot be ignored. Twitter is no different, and every change in leadership has seen a change in the organization and the product. Today, Twitter awaits its next leader, at a time when employees are quitting, users are not happy and share prices are dropping. The case traces the leadership journey at Twitter.